Overview of breast cancerpatients and their prognostic factors treated in Baghdad teaching hospital/ oncology department in the year 2010 - Al Naqqash, Manwar A. (Journal of the Faculty of Medicine Baghdad, 2011)
Background:The breast cancer is the most common non-skin malignancy in women and prognostic factors are important in predicting disease free survival and overall survival. Objective: To detect prognostic factors of breast cancer patients and study the correlation between these prognostic factors. Patients and methods: this is a retrospective study which included87 patients with breast cancer receiving chemotherapy in Baghdad teaching hospital/ oncology department in the year 2010. Prognostic factors were registered including: age, histopathological subtype, degree of differentiation, lymph node involvement, ER and PR, Her 2/neu and lymphovascular invasion. Results: Regarding breast cancer; 55(63.2%) of patients were early breast cancer as compared to32(36.8%)patients with locally advanced breast cancer.Regarding lymph node involvement 31(36.9%) of patients had N0,28(33.3%) had N1, 23(27.4%) had N2 and 2(2.4%) were with N3. Regarding degree of differentiation the most common type was moderately differentiated with 58(66.7%) followed by poorly differentiated with 23 (26.4%) and at last well differentiated tumors with 6(6.9%) patients. Infiltrative ductal carcinoma was the most common subtype other histopathological subtypes as infiltrative lobular carcinoma (13.8%) and medullary carcinoma (2.3%). Intraductal carcinoma were present in 23 cases (25.8%).ER was negative in 33% and PR was negative in 37.5% while the remaining cases shows positivity with different percentage scores.Cross tabulation between different prognostic factors ( tumor size, lymph node, degree of differentiation, lymphovascular invasion) were done and results were statistically not significant, regarding ER and PR showed strong significant correlation( p < 0.0005).between the two markers also significant correlation was found between lymphovascular invasion and lymph nodes involvement. Conclusion: breast cancer is the most common solid malignancy treated in Baghdad teaching hospital. Early stage breast cancer were more common than advanced breast cancer, ER and PR(good prognostic factors) were statistically correlated to each other so were lymphovascular invasion with lymph nodes involvement(bad prognostic factors).